The impact of robots on labour market transitions in Europe - Ronald Bachmann; Myrielle Gonschor; Piotr Lewandowski; Karol Madoń (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
We study the effects of robot exposure on worker flows in 16 European countries. Overall, we find small negative effects on job separations and small positive effects on job findings. Labour costs are shown to be a major driver of cross-country differences: the effects of robot exposure are generally larger in absolute terms in countries with low or average levels of labour costs than in countries with high levels of labour costs. These effects were particularly pronounced for workers in occupations intensive in routine manual or routine cognitive tasks, but were insignificant in occupations intensive in non-routine cognitive tasks. For young and old workers in countries with lower labour costs, robot exposure had a beneficial effect on transitions. Our results imply that robot adoption increased employment and reduced unemployment most in the European countries with low or average levels of labour costs. – – Dieses Papier untersucht die Auswirkungen von Robotern auf Arbeitsmarkttransitionen in 16 europäischen Ländern. Generell reduzieren Roboter Übergänge von der Beschäftigung in die Arbeitslosigkeit und erhöhen die Wahrscheinlichkeit, einen neuen Job zu finden. Arbeitskosten sind eine wichtige Erklärung für die beobachteten Unterschiede zwischen Ländern: In Ländern mit niedrige oder durchschnittlichen Arbeitskosten zeigt sich ein stärkerer Effekt auf Einstellungen und Trennungen als in Ländern mit hohen Arbeitskosten. Diese Auswirkungen sind bei Arbeitskräften in Berufen mit manuellen oder kognitiven Routineaufgaben besonders ausgeprägt, bei Berufen mit nicht-kognitiven Routineaufgaben hingegen vernachlässigbar. Für junge und ältere Arbeitskräfte in Ländern mit niedrigeren Arbeitskosten wirken sich Roboter positiv auf Übergänge aus. Unsere Ergebnisse deuten darauf hin, dass die Einführung von Robotern zu einem Anstieg der Beschäftigung und einem Rückgang der Arbeitslosigkeit geführt hat, vor allem in Ländern mit niedrigen oder durchschnittlichen Arbeitskosten.
Keywords: J24; O33; J23; 330; Robots; technological change; tasks; labour market effects; Europe